Standar mutu pengelolaan pembelajaran ekstrakurikuler karawitan studi kasus di sekolah dasar - Aini, Adinda Nur; Marmoah, Sri; Budiharto, Tri (Didaktika Dwija Indria, 2025)
This research uses a qualitative approach with a case study method to explore in depth the quality standards in the management of extracurricular music programs at SD Negeri Palur 02. The purpose of this research is to understand how extracurricular music learning is managed in terms of educational quality standards. Data collection techniques included observation, interviews and documentation, with data validation using triangulation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that the management of extracurricular karawitan learning at SD Negeri Palur 02 has successfully fulfilled various educational quality standards stipulated in the National Education Standards, including Graduate Competency Standards, Content Standards, Process Standards, Educator Standards, Facilities and Infrastructure Standards, Management Standards, Financing Standards, and Assessment Standards. The implications of this research consist of theoretical implications: This research enriches the literature on the application of the National Education Standards in extracurricular activities and develops an effective learning management model. Practical Implications: The findings provide practical guidance for schools in managing extracurricular activities as well as input for education policy regarding budget and resource allocation.